New design of a linear double‐sided printed dipole array based on bat algorithm for interference suppression in the first sidelobe direction. Issue 12 (21st July 2020) - Truong, Luong Xuan; Vu‐Bang Giang, Truong; Tuan, Tran Minh
Abstract : This study proposes a design of a double‐sided printed dipole (DSPD) antenna array with a low first sidelobe level (FSLL) for interference suppression. The proposed array consists of ten DSPD antennas based on the Rogers RO4003C substrate ( ɛr = 3.55). The FSLL has been compressed by imposing a single null at the centre of the first sidelobe. The excitation power distribution of the array has been calculated by using the bat algorithm with the amplitude‐only control technique and has been implemented by a series‐fed network. A back reflector, which is based on an FR4 substrate ( ɛr = 4.4), has been used to improve the maximum gain. The simulation results show that the FSLL can be reduced with a null deep level (NDL) of −40 dB in the E ‐plane at the frequency of 3.5 GHz, while the maximum gain of the array is around 17.7 dBi, and the bandwidth is 600 MHz (3.3–3.9 GHz) with −10 dB of S 11 . A prototype of the proposed DSPD antenna array has been fabricated and measured. A good agreement can be achieved between simulation and measurement results.